Robotic locomotor training for spasticity, pain, and quality of life in individuals with chronic SCI: A pilot randomized controlled trial - Shackleton, Claire; Evans, Robert; West, Sacha; Derman, Wayne; Albertus, Yumna (Frontiers in Rehabilitation Sciences, 2023)
Objective The prevention and treatment of secondary complications is a key priority for people with spinal cord injury and a fundamental goal of rehabilitation. Activity-based Training (ABT) and Robotic Locomotor Training (RLT) demonstrate promising results for reducing secondary complications associated with SCI. However, there is a need for increased evidence through randomized controlled trials. Therefore, we aimed to investigate the effect of RLT and ABT interventions on pain, spasticity, and quality of life in individuals with spinal cord injuries. Methods Participants with chronic motor incomplete tetraplegia (n = 16) were recruited. Each intervention involved 60-minute sessions, 3× per week, over 24-weeks. RLT involved walking in an Ekso GT exoskeleton. ABT involved a combination of resistance, cardiovascular and weight-bearing exercise. Outcomes of interest included the Modified Ashworth Scale, the International SCI Pain Basic Data Set Version 2, and the International SCI Quality of Life Basic Data Set. Results Neither intervention altered symptoms of spasticity. Pain intensity increased from pre-post intervention for both groups, with a mean increase of 1.55 [−0.82, 3.92] (p = 0.03) and 1.56 [−0.43, 3.55] (p = 0.02) points for the RLT and ABT group, respectively. The ABT group had an increase in pain interference scores of 100%, 50%, and 109% for the daily activity, mood, and sleep domain, respectively. The RLT group had an increase in pain interference scores of 86% and 69% for the daily activity and mood domain respectively, but no change in the sleep domain. The RLT group had increased perceptions of quality of life with changes of 2.37 [0.32, 4.41], 2.00 [0.43, 3.56] and 0.25 [−1.63, 2.13] points, p = 0.03, for the general, physical, and psychological domains, respectively. The ABT group had increased perceptions of general, physical and psychological quality of life with changes of 0.75 [−1.38, 2.88], 0.62 [−1.83, 3.07] and 0.63 [−1.87, 3.13] points, respectively. Conclusions Despite increased pain ratings and no change in symptoms of spasticity, there was an increase in perceived quality of life for both groups over 24-weeks. This dichotomy warrants additional investigation in future large-scale randomized controlled trials.